MANUFACTURING PROCESS RUBBER TIRE - Carrión Nin, José Luis (1999)
In this synthesis, developing a brief explanation about the preparation, construction and manufacturing methods of the manufacturing process of rubber tires. While brief, this information will provide a comprehensive and simple idea of the manufacturing process that in itself is interesting. The features of the process are shown in a diagram. The initial phase of the process is the preparation of the rubber, this is initiated by mixing the components in accordance with a scientific formula. Alongside the various components that make up the structure of the tire are made. Finally, a rigorous quality control of the finished product is essential to successfully ensure durability.